Stability and reconstitution of pyruvate oxidase from Lactobacillus plantarum: dissection of the stabilizing effects of coenzyme binding and subunit interaction. - Risse, B. (Cold Spring Harbor Laboratory Press, 1992)
Pyruvate oxidase from Lactobacillus plantarum is a homotetrameric flavoprotein with strong binding sites for FAD, TPP, and a divalent cation. Treatment with acid ammonium sulfate in the presence of 1.5 M KBr leads to the release of the cofactors, yielding the stable apoenzyme. In the present study, the effects of FAD, TPP, and Mn2+ on the structural properties of the apoenzyme and the reconstitution of the active holoenzyme from its constituents have been investigated. As shown by circular dichroism and fluorescence emission, as well as by Nile red binding, the secondary and tertiary structures of the apoenzyme and the holoenzyme do not exhibit marked differences. The quaternary structure is stabilized significantly in the presence of the cofactors. Size-exclusion high-performance liquid chromatography and analytical ultracentrifugation demonstrate that the holoenzyme retains its tetrameric state down to 20 micrograms/mL, whereas the apoenzyme shows stepwise tetramer-dimer-monomer dissociation, with the monomer as the major component, at a protein concentration of < 20 micrograms/mL. In the presence of divalent cations, the coenzymes FAD and TPP bind to the apoenzyme, forming the inactive binary FAD or TPP complexes. Both FAD and TPP affect the quaternary structure by shifting the equilibrium of association toward the dimer or tetramer. High FAD concentrations exert significant stabilization against urea and heat denaturation, whereas excess TPP has no effect. Reconstitution of the holoenzyme from its components yields full reactivation. The kinetic analysis reveals a compulsory sequential mechanism of cofactor binding and quaternary structure formation, with TPP binding as the first step. The binary TPP complex (in the presence of 1 mM Mn2+/TPP) is characterized by a dimer-tetramer equilibrium transition with an association constant of Ka = 2 x 10(7) M-1. The apoenzyme TPP complex dimer associates with the tetrameric holoenzyme in the presence of 10 microM FAD. This association step obeys second-order kinetics with an association rate constant k = 7.4 x 10(3) M-1 s-1 at 20 degrees C. FAD binding to the tetrameric binary TPP complex is too fast to be resolved by manual mixing.